Experimental and numerical characterization of titanium-based fibre metal laminates. (1st August 2020) - Nassir, Nassier.A.; Birch, R.S.; Cantwell, W.J.; Sierra, D. Rico; Edwardson, S.P.; Dearden, G.; Guan, Z.W.
Highlights: Quasi-static and Impact perforation of titanium-based fibre metal laminates. A laser fluence of 5.54 J/cm 2 on the titanium layers gives a good bond strength. Finite element modelling of perforation failure of the FMLs. Good correlation between the experimental and simulated results. Capture load–displacement traces and failure modes of the FMLs. Abstract: The effect of applying a laser surface treatment to the metal plies in a fibre metal laminate (FML) based on a titanium alloy and a fibre reinforced composite has been evaluated and the response compared to that measured on a comparable untreated laminate. It has been shown that applying a laser fluence of 4.54 J/cm 2 to the titanium layers in the FML results in a good bond strength between the titanium foil and the glass fibre/PEKK composite. The response of the FMLs under dynamic loading was studied and compared with that measured at quasi-static rates. It has been shown that FMLs based on a titanium alloy exhibit a rate-sensitivity, both in terms of energy absorption and the maximum impact force. An examination of cross-sections removed from samples following testing at dynamic and quasi-static loading rates indicated that the FMLs absorbed energy through plastic deformation, tearing of the metal layers, delamination and fibre fracture. Finite element models were then developed to simulate the response of the FMLs under impact loading. The simulated results were validated against the corresponding experimental data by comparing both the load–displacement traces as well as the resulting failure modes, with good agreement being observed in most cases.